MANAGEMENT ACCOUNTING AS A MODERN ACCOUNTING PARADIGM OF THE BUDGETARY INSTITUTIONS - MARIA Vakhruchina (Учёт. Анализ. Аудит)
Russian budgetary institutions operate in the difficult economic conditions. On the one hand, the rate of the growth of budgetary institutions financing from the government decreases, on the other hand, the budgetary institutions, according to their status, are obliged to achieve their social objectives and successfully complete government-approved social programs. The continued reform of state-owned sector of the economy and the expansion of economic and financial autonomy of the state (municipal) institutions requires the theoretical substantiation and the development of recommendations on the organization of management accounting in state (municipal) institutions.Referring to the process analysis of the formation and development of management accounting in budgetary institutions taking into consideration the specifics of its activity as well as the modern trends of its international development, the article clarifies the theoretical and methodological foundations of management accounting (its purpose, objectives, principles, objects). An attempt was made to adapt the concept of “business model” to the activities of the Russian budgetary institutions. The functional responsibilities and the competence of an accountant-analyst of modern budgetary institutions were defined.